Hydroxyl Transfer to Carbon Radicals by Mn(OH) vs Fe(OH) Corrole Complexes - Daniel C. Cummins,; Jessica G. Alvarado,; Jan Paulo T. Zaragoza,; Yen-Ting Lin,; Sam P. de Visser; David P. Goldberg; Muhammad Qadri Effendy Mubarak (American Chemical Society, 2024)
Inorg. Chem. 2020, 59, 21, 16053–16064 Publication Date:October 13, 2020 https://doi.org/10.1021/acs.inorgchem.0c02640